Absence of antibody to HTLV I and III in sera of Canadian patients with multiple sclerosis and chronic myelopathy. - Rice, G; Armstrong, H; Bulman, D; Paty, D; Ebers, G (1986)
Recently, elevated titers of antibody to HTLV I have been demonstrated in patients with tropical spastic paraparesis and multiple sclerosis. We evaluated the possible role of human retroviruses HTLV I and III in Canadian patients with multiple sclerosis and chronic idiopathic myelopathy. Using sensitive enzyme immunoassays, we were unable to find antibody to either HTLV I or III in 201 patients with multiple sclerosis, 29 patients with chronic myelopathy, 51 patients with other neurological disorders, or 29 normal subjects. These data do not support a role for these viruses in the cause of sporadic multiple sclerosis and chronic myelopathy in a regionally based Canadian population, but do not exclude a role for other antigenically distinct retroviruses.